Ethnic Immigration Policy Implementation (1992- 2009) - Amangul, Shugatai (Mongolian Journal of International Affairs, 2013)
After Kazakhstan declared its independence, it became a large performer in the worldwide international migration process. The attraction of social and economic stability (with an increase in the level of living standard), stable ethno-demographic and population growth, no nationalist struggles as well as positive geopolitical situations, have lead to a huge flow of immigrants to Kazakhstan in the years since independence. In this study, I have suggested that results of the ethnic immigration policy include strengthening the national identity, creating a positive effect on the ethno-demographic outcomes, and increasing the number of the population size over the last nineteen years. DOI: http://dx.doi.org/10.5564/mjia.v0i17.87 Mongolian Journal of International Affairs, No.17 2012: 109-117